Identification of MS-specific serum miRNAs in an international multicenter study. Issue 5 (September 2018) - Regev, Keren; Healy, Brian C.; Paul, Anu; Diaz-Cruz, Camilo; Mazzola, Maria Antonietta; Raheja, Radhika; Glanz, Bonnie I.; Kivisäkk, Pia; Chitnis, Tanuja; Jagodic, Maja; Piehl, Fredrik; Olsson, Tomas; et al.
Abstract : Objective: To identify circulating microRNAs (miRNAs) linked to disease, disease stage, and disability in MS across cohorts. Methods: Samples were obtained from the Comprehensive Longitudinal Investigation of Multiple Sclerosis (CLIMB, Boston, MA), EPIC (San Francisco, CA), AMIR (Beirut, Lebanon) as part of the SUMMIT consortium, and Stockholm Prospective Assessment of Multiple Sclerosis (Stockholm, Sweden) cohorts. Serum miRNA expression was measured using locked nucleic acid–based quantitative PCR. Four groups were compared: (1) MS vs healthy control (HC), (2) relapsing-remitting (RR) vs HC, (3) secondary progressive (SP) vs HC, and (4) RR vs SP. A Wilcoxon rank-sum test was used for the comparisons. The association between each miRNA and the Expanded Disability Status Scale (EDSS) score was assessed using the Spearman correlation coefficient. For each comparison, the p values were corrected for multiple comparisons using the approach of Benjamini and Hochberg to control the false discovery rate. Results: In the CLIMB cohort, 5 miRNAs (hsa-miR-484, hsa-miR-140-5p, hsa-miR-320a, hsa-miR-486-5p, and hsa-miR-320c) showed a significant difference between patients with MS and healthy individuals; among these, miR-484 remained significant after accounting for multiple comparisons ( p = 0.01). When comparing RRMS with HCs, hsa-miR-484 showed a significant difference ( p = 0.004) between the groups after accounting for multiple group comparisons. When SP and HC were compared, 6 miRNAs (hsa-miR-484, hsa-miR-140-5p, hsa-miR-142-5p, hsa-miR-320a, hsa-miR-320b, and hsa-miR-320c) remained significantly different after accounting for multiple comparisons. Disability correlation analysis with miRNA provided 4 miRNAs (hsa-miR-320a, hsa-miR-337-3p, hsa-miR-199a-5p, and hsa-miR-142-5p) that correlated with the EDSS during the internal reproducibility phase. Among these, hsa-miR-337-3p was the most statistically significant miRNA that negatively correlated with the EDSS in three of the MS cohorts tested. Conclusions: These findings further confirm the use of circulating serum miRNAs as biomarkers to diagnose and monitor disease status in MS. Classification of evidence: This study provides Class III evidence that levels of circulating miRNAs identify patients with MS.